Proposed Marketing Strategy for Edward Forrer - Busra, Ria Agustriana; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2015)
Abstract— Competition in the footwear business is quite intense because shoes are not only considered footwear, but it also has become a fashion product that complements the wearer’s appearance in their daily life. Edward Forrer (EF), a local footwear company from Bandung that located in Jalan Ir.H. Djuanda and is also known as Dago where the location were expected to increase sales for Edward Forrer. However, this prediction failed as it had little significance on the volume of sales. Edward Forrer faces the situation where their sales revenue of footwear products in the Dago outlet has fluctuated and has tended to decline year to year Conceptual framework in this functioned as an outline to explain steps that taken by the author in this final project. The survey method through questionnaire applied in this study to gain an insight, a description from respondents related to existing symptoms that happens, find accurate facts that can be used to formulate strategy of what steps that company should take in order to stay in competition and survive. In internal analysis found Edward Forrer STP was improper, lack of promotion, and unattractive outlet design. Marketing mix that run by EF become ineffective to attract customer. External analysis conducted to get an insight of the environment situation and conditions in which the company compete by using 4C’s analysis. Compare to its competitor, Edward Forrer has the lowest score in quality of material, footwear design, price of footwear, variety colors, and customer considered that they price is not compatible with the product. In chapter three, the author suggested strategy for Edward Forrer based on analysis performed is brand revitalization strategy using two approach. First, it is to expand the depth or breadth (or both) of brand awareness by improving brand recall and recognition by consumers during the purchase or consumption settings. Second, is to improve the strength, favorability, and uniqueness of brand association by making up the brand image from these approaches. This two approach explained by make new STP and marketing mix.The implementation consist of the planning activities and the implementation plan. Edward Forrer revitalization, can be divide to two stages. The first stage is to fix the current condition of Edward Forrer outlet. Stage two is to communicate the new Edward Forrer, increase brand awareness and sales.Keywords: footwear, marketing strategy, Edward Forrer